Association between energy/protein adequacy and quality of life among critically ill survivors./ Mazuin Kamarul Zaman ... [et al.] - Kamarul Zaman, Mazuin; Mat Din, Mardhiah; Tah, Pei Chien; Hasan, Mohd Shahnaz (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
Medical advancements decrease mortality rate of critically ill patients over time. However, there are increasing number of patients discharged to nursing home and rehabilitation centers. Energy and protein deficit along with hypercatabolism during the period of critical illness may lead to malnutrition and poorer clinical outcomes. This study aims to investigate the association between energy and protein adequacy with and quality of life of Intensive Care Unit (ICU) survivors. Prospective observational study was conducted to follow ICU survivors from ICU admission day to a year post-admission. Convenience sampling was employed for study’s enrollment. Energy and protein adequacy during critical illness were obtained from nutritional intake in ICU ward from admission day until patients were discharged of ICU or maximum of 14 days. Quality of life was measured using SF-12 and EuroQoL-5D-3L questionnaires through a phone interview. Of 189 patients followed, 105 patients were alive at 1-year post ICU admission. Only 26 ICU survivors with a median age of 52.3 (18-83) years old were able to be reached. Most of the critically patient received an adequate intake of energy (93%), protein (86.7%), and energy and protein (76.9%). 85% of ICU survivors reported poor quality of life. There was no association between energy adequacy (p=0.158), protein adequacy (p=0.921), energy and protein adequacy (p=0.921) and the quality of life. This study showed that most critically ill patients were adequately nourished during the ICU stay and there was no association between energy and protein adequacy and quality of life of 1-year ICU survivors.